2019
DOI: 10.3390/nu11102282
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Nutrient Profiling of Retail Goat and Cow Milk

Abstract: Goat milk is globally consumed but nutritional profiling at retail level is scarce. This study compared the nutrient composition of retail cow and goat milk (basic solids, fatty acids, minerals, and phytoestrogens) throughout the year and quantified the potential implications on the consumers’ nutrient intakes. When compared to cow milk, goat milk demonstrated nutritionally desirable traits, such as lower concentrations of C12:0, C14:0, C16:0 and Na: K ratio, and the higher concentrations of cis polyunsaturate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
39
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 68 publications
(191 reference statements)
10
39
3
1
Order By: Relevance
“…The mineral profile of this study coincides with that shown by Stergiadis et al [47]. The Ca/P ratio of BB and AP animals is similar to that observed in local breeds in southern Europe [48,49]. The Ca/P ratio of C animals was lower due to its lower Ca content.…”
Section: Milk Mineral Profilesupporting
confidence: 90%
“…The mineral profile of this study coincides with that shown by Stergiadis et al [47]. The Ca/P ratio of BB and AP animals is similar to that observed in local breeds in southern Europe [48,49]. The Ca/P ratio of C animals was lower due to its lower Ca content.…”
Section: Milk Mineral Profilesupporting
confidence: 90%
“…The comparative macronutrient features of goat and cow milk have been reviewed previously (Ceballos et al., 2009; Clark & Mora Garcia, 2017; Jenness, 1980; Stergiadis, Nørskov, Purup, Givens, & Lee, 2019) and hence will not be dealt with extensively here. The key nutrients that are different between the two milks important in the context of infant nutrition are summarized in Table 1 and discussed in more detail in the following sections.…”
Section: Composition Of Goat Milkmentioning
confidence: 99%
“…Konsumsi susu dapat menurunkan tekanan darah sebanyak 50% (22). Kandungan kalsium dan juga sejumlah zat bioaktif yang ada pada susu berperan dalam memodulasi tekanan darah (35)(36)(37)(38).…”
Section: Desain Dan Subjekunclassified